Oxygen Consumption Rates during Three Different Neuronal Activity States in the Hippocampal CA3 Network. Issue 2 (February 2013) - Huchzermeyer, Christine; Berndt, Nikolaus; Holzhütter, Hermann-Georg; Kann, Oliver
The brain is an organ with high metabolic rate. However, little is known about energy utilization during different activity states of neuronal networks. We addressed this issue in area CA3 of hippocampal slice cultures under well-defined recording conditions using a 20% O2 gas mixture. We combined recordings of local field potential and interstitial partial oxygen pressure (pO2 ) during three different activity states, namely fast network oscillations in the gamma-frequency band (30 to 100 Hz), spontaneous network activity and absence of spiking (action potentials). Oxygen consumption rates were determined by pO2 depth profiles with high spatial resolution and a mathematical model that considers convective transport, diffusion, and activity-dependent consumption of oxygen. We show that: (1) Relative oxygen consumption rate during cholinergic gamma oscillations was 2.2-fold and 5.3-fold higher compared with spontaneous activity and absence of spiking, respectively. (2) Gamma oscillations were associated with a similar large decrease in pO2 as observed previously with a 95% O2 gas mixture. (3) Sufficient oxygenation during fast network oscillations in vivo is ensured by the calculated critical radius of 30 to 40 μ m around a capillary. We conclude that the structural and biophysical features of brain tissue permit variations in local oxygen consumption by a factor of about five.